2022
DOI: 10.3390/healthcare10040680
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Balance Exercise Using Virtual Reality for Rehabilitation

Abstract: To prevent falls, it is important to devise a safe balance training program that can be easily performed. This study investigated whether tilting an image in virtual reality (VR) can generate a center-of-gravity sway. Five men and five women were asked to rest standing upright (control condition) and to rest standing upright with a head-mounted display showing a tilted virtual image (VR condition), and changes in their standing balance were observed. Standing balance was assessed by measuring the distance trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to a meta-analysis by Sherrington et al [ 22 ] in fall prevention, we can see better relative effects in programs that improve balance, are more intense and do not include a walking program. There is increasing use of virtual reality in rehabilitation [ 23 , 24 , 25 , 26 ]. The question to ask is how the patient should perform the exercises in order for them to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis by Sherrington et al [ 22 ] in fall prevention, we can see better relative effects in programs that improve balance, are more intense and do not include a walking program. There is increasing use of virtual reality in rehabilitation [ 23 , 24 , 25 , 26 ]. The question to ask is how the patient should perform the exercises in order for them to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…COG trajectory analysis is not only used for testing; adding COG perturbations is also an important means of balancing training. Urabe et al [14] used virtual reality (VR) technology to induce swaying of the COG by allowing subjects to experience body tilting and loss of balance in a virtual space, indicating a significant increase in the subject's ability to withstand external perturbations. Runge [15] found that increasing the platform velocity and greater COG interference during balance training might aid recovery of the balance function to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has also shown that training in VR using an HMD could be useful for fall prevention and postural control in older people; however, there are concerns that the research in older people is of poor quality due to challenges in ensuring safety and a high risk of bias [9]. Urabe et al used an HMD to demonstrate fluctuations in the center-of-gravity sway during a static standing posture in younger adults [10]. This study was a milestone compared to conventional balance training in terms of safety, which induces center-of-gravity sway during stationary standing without physical movement but was limited to a young cohort.…”
Section: Introductionmentioning
confidence: 99%